The Teaching Of English In Sdii Nurul Mustofa Juwiring, Klaten(A Naturalistic Study) - Ariyani, Rima (2004)
in SDII Nurul Mustofa, (2) To know the type of syllabus that is used in SDII Nurul Mustofa, (3) To know the procedure of teaching and learning activities in SDII Nurul Mustofa, (4) To know the role of material that is used in SDII Nurul Mustofa, (5) To know the roles of teacher and students in SDII Nurul Mustofa. This research has taken place at SDII Nurul Mustofa in Troditan, Bolopleret, Juwiring, Klaten especially third grade students. The third grade students of SDII Nurul Mustofa consist of two classes A and B. the writer chooses B class that consist of thirty-four students to observe. In this research, the data are collected from event, informant, and document. There are three techniques of collecting the data namely: observation, interview, and document analysis. This research is using constant comparative in analyzing the data that includes four steps: comparing unit to each category, integrating categories and their properties, delimiting the theory, and writing the theory. It appears from the research that the objective of teaching is consistent with communicative approach and it is suitable with other experts' theory on teaching English. The syllabus is not taken from the curriculum but from the guidebook. The book is used as the orientation and material in SDII Nurul Mustofa. Type of syllabus is topic-based syllabus that consists of theme and sub theme. While type and procedure of teaching and learning process, the role of instructional materials and the role of teacher and students are suitable with the experts' theory. The activities in teaching learning process include four language skills (speaking, listening, reading, and writing) The writer proposes base on the research findings above, in order to get better out put in teaching English. (a) For the teacher, she/he should be able to make students active in speaking. The teacher should improve her/his ability in performing in teaching, lead more book in teaching method by reading more book. (b) For the other researchers, there is point that can be observed and developed. Teaching English at Elementary school can be observed deeply, whether the English lesson is suitable or not taught in Elementary School. In other prospective researcher may use the findings to enlarge and deepen further research.